2020
DOI: 10.1080/08952841.2020.1845563
|View full text |Cite
|
Sign up to set email alerts
|

The sociocultural relationships of older immigrant Punjabi women living in Nova Scotia: Implications for well-being

Abstract: With the increase of South Asian immigrants in Canada, the relationship between older immigrant Punjabi women's sociocultural relationships and their mental health and well-being needs to be understood. Guided by the social determinants of health and intersectional feminist frameworks, five Punjabi women living in Nova Scotia, Canada were interviewed. Three themes were identified: (a) having freedom yet being dependent on families, (b) conflating having a happy family with having good mental health, and (c) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Lifestyle seekers migrate to destinations offering improved quality of life through factors such as better weather ( Mullins & Tucker, 1992 ), lower cost of living ( Karacan, 2020 ), and better access to facilities ( Sah et al, 2018 ). The primary motivation for family reunification is to be close to adult children ( Caidi et al, 2020 ; Chiu & Ho, 2020 ; Dhillon & Humble, 2020 ; Girgis, 2020 ; Park & Kim, 2013 ; Serafica & Thomas Reyes, 2019 ; Stewart et al, 2011 ; Treas, 2008 ), highlighting the importance of social relationships and connections in the migration decision-making process. Family reunification studies either focused on temporary migration and the transnational lifestyle of migrants ( Chiu & Ho, 2020 ) or a combination both of permanent and temporary migration ( Hamilton et al, 2021 ; Treas & Mazumdar, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lifestyle seekers migrate to destinations offering improved quality of life through factors such as better weather ( Mullins & Tucker, 1992 ), lower cost of living ( Karacan, 2020 ), and better access to facilities ( Sah et al, 2018 ). The primary motivation for family reunification is to be close to adult children ( Caidi et al, 2020 ; Chiu & Ho, 2020 ; Dhillon & Humble, 2020 ; Girgis, 2020 ; Park & Kim, 2013 ; Serafica & Thomas Reyes, 2019 ; Stewart et al, 2011 ; Treas, 2008 ), highlighting the importance of social relationships and connections in the migration decision-making process. Family reunification studies either focused on temporary migration and the transnational lifestyle of migrants ( Chiu & Ho, 2020 ) or a combination both of permanent and temporary migration ( Hamilton et al, 2021 ; Treas & Mazumdar, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…This research aligns with the small number of other studies conducted with migrant populations in Australia and internationally. Other studies have highlighted the importance of independence [ 18 , 19 ] and social connections [ 20 , 21 ] to older adults from CALD backgrounds. The quality-of-life dimension of having a meaningful role identified in a previous study [ 18 ] was similar to the dimension of ‘purpose and meaning’ identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, small samples sizes for research with non-English speaking older adults is common given the challenge of recruiting and the costs of hiring interpreters. The studies conducted in other English-speaking nations with Asian older adults had interview sample sizes of between 5 and 30 [ 18 , 20 ], and a previous survey study had a sample size of 79 [ 21 ]. Additionally, as previously mentioned COVID-19 created significant barriers to gaining support for recruitment at a time when aged care providers had many additional demands placed on them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather surprisingly, these friendships formed regardless of how actively the women participated in the fitness portion of the program, suggesting that the fitness program context had unintended, albeit equally important, effects on their sense of connection. Exploring the cultural milieu of older women's sense of connection, Dhillon and Humble (2021) examined how five older Punjabi women who had immigrated to Nova Scotia interpreted their social ties. Underscoring the complexity of our closest ties, these women shared the tensions they felt between wanting to be independent but feeling overly reliant on their families, while also highlighting how their family's happiness was integral to their own well-being.…”
Section: Editorialmentioning
confidence: 99%